(untitled) (Albayan Scientific Journal, 2023)
Administrations of dehydroepiandrosterone (DHEA) to female had effects on ovarian response ovarian reserve, oocytes embryo yield quality, cumulus pregnancy rate, live birth rate and also improved the miscarriage rate and improve the results of infertility treatment. The aim of present study is to examine the replenishing effect of dehyroepiandrosteron (DHEA) on the reprotoxicity induced by exposure to vinylcyclohexene diepoxide (VCD) on mature female rats. 48 mature female rats were divided into equal four groups. The control group was injected intraperitoneally with sesame oil (0.2 ml) daily for 45 days. The second group was injected with DHEA (0.2 ml) once daily for 45 days. The third group was injected with VCD (1.2 ml) once daily for 45 days. The fourth group was injected with DHEA (0.2 ml) +VCD (1.2 ml) once daily for 45 days. Results showed that the DHEA treated females was close to the control rats in most of the measured plasma hormone levels, except DHEA and CORT hormones. While the group treated with VCD recorded a significant decrease (P<0.05) in most of the hormones (P4, E2, FSH, LH, INS and DHEA) except the CORT hormone. It should be noted that the gradual improvement that occurred as a result of giving DHEA to females treated with VCD in the levels of all hormones as compared with control rats. Histopathological examination of female rat ovaries in VCD group showing atrophied primordial follicle with pyknotic nuclei. DHEA group reveals normal primordial follicle with owl eye nuclei. DHEA+VCD group revealing normal primary follicle with owl eye nuclei. From present study it could be concluded that administration of DHEA to female rat affecting on reproductive function, it is important precursor steroid to synthesis of the sex steroid and is changed to androgens or estrogens. The estrogens stimulate the ovaries and increase growth of the follicles and proliferation of granulosa cell and development.